Keeping The Lights On - Clancy, Heather (CRN, 2004)
As embedded system integrators increasingly adopt commercial, off-the-shelf component sourcing strategies and bring third parties into their integration processes and supply chains, they are shining a brighter light on the need for intellectual property (IP) protection. S4 Group has invested in hiring legal counsel with experience in international sourcing policies, since many of its key relationships are with multinational suppliers, distributors and integration partners. S4 Group has set clear parameters for where its technology starts and ends. AMX subjects its supplier relationships to especially stringent scrutiny to ensure that its component vendors have their own IP measures in place and, if not, that they will indemnify AMX against any claims. It is also important for companies to instill the value of protection not just in a few top executives but in their entire workforce, according to Venturcom director Will Hornkohl.